Effect of ciprofol–etomidate mixtures for deep sedation during gastrointestinal endoscopy: Protocol for a three-arm, double-blind randomized controlled trial - Boxuan Xu; Min Niu; Xueling Zhu; Min Cui; Xiaona An; Tianhao Yu; Sihui Tang; Qiuyu Yang; Junjie Wang; Jiguo Si (PLoS ONE, 2026)
Introduction Deep sedation for gastrointestinal endoscopy can be achieved using either ciprofol or etomidate, both associated with distinct adverse events such as cardiopulmonary depression, myoclonus, and postoperative nausea and vomiting. This study aims to evaluate the safety and efficacy of two ciprofol–etomidate mixtures at varying volume ratios compared with ciprofol alone in patients undergoing gastrointestinal endoscopy. Methods This three-arm prospective study will include 135 participants aged 18–65 years who are scheduled for gastrointestinal endoscopy under deep sedation. Patients will be randomly assigned in a 1:1:1 ratio to receive either ciprofol alone or a ciprofol–etomidate mixture at volume-to-volume ratios of 1:1 or 2:1. The primary outcome is the composite incidence of various adverse events, including hypotension, hypoxemia, bradycardia, tachycardia, injection site pain, myoclonus, and nausea and vomiting. The secondary outcomes include the success rate of sedation, induction time, awakening time, recovery time, vital signs, and patient satisfaction. Analyses will be conducted using intention-to-treat and per-protocol approaches. Discussion This three-arm randomized controlled trial will determine the potential benefits of combining ciprofol with etomidate for deep sedation during gastrointestinal endoscopy, with a focus on enhanced cardiopulmonary stability, reduced injection site pain, decreased incidence of myoclonus, and lower rates of nausea and vomiting. Trial registration This trial has been registered on ChiCTR.gov.cn (ChiCTR2400093109), on Nov 28, 2024.